2012
DOI: 10.1097/acm.0b013e3182712cff
|View full text |Cite
|
Sign up to set email alerts
|

The Development, Implementation, and Assessment of an Innovative Faculty Mentoring Leadership Program

Abstract: Effective mentoring is an important component of academic success. Few programs exist to both improve the effectiveness of established mentors and cultivate a multi-specialty mentoring community. In 2008, in response to a faculty survey on mentoring, leaders at Brigham and Women’s Hospital developed the Faculty Mentoring Leadership Program (FMLP) as a peer-learning experience for mid-career and senior faculty physician and scientist mentors to enhance their skills and leadership in mentoring and create a suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 23 publications
(21 reference statements)
1
61
0
4
Order By: Relevance
“…Requirements for the position included a clear interest in serving, guaranteed time commitment to fulfil the duties of the committee, and agreement to serve as the point person for communication of all requirements and aspects of the award at their centre. 16 The nine core centre representatives included three assistant professors, three associate professors, and three professors who also served as the selection panel for the award. The equal distribution in rank allowed input on the process and review across the spectrum of junior to senior investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Requirements for the position included a clear interest in serving, guaranteed time commitment to fulfil the duties of the committee, and agreement to serve as the point person for communication of all requirements and aspects of the award at their centre. 16 The nine core centre representatives included three assistant professors, three associate professors, and three professors who also served as the selection panel for the award. The equal distribution in rank allowed input on the process and review across the spectrum of junior to senior investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Giving and receiving positive feedback is much easier than negative feedback-even when meant to be helpful. 9,10 In addition, to be effective, feedback must be provided in a timely fashion along with an organized process to monitor progress.…”
Section: Assessing Feedback From Mentors and Menteesmentioning
confidence: 99%
“…[25][26][27][28][29][30] Validated assessment is needed to demonstrate impact and compare curriculum. 9,14,[31][32][33][34][35][36][37][38][39][40][41][42] A systematic review of leadership training in health care teams found that defining best practices is difficult due to lack of a standard definition of leadership, supporting frameworks, and robust assessments. 35 Though assessments do exist for health care administrators, practicing physicians, and surgeons' nontechnical skills in the operating room (including leadership), there are no published assessment instruments of leadership skills for physicians in residency training programs.…”
Section: Original Articlesmentioning
confidence: 99%